EVALUASI WEBSITE DENGAN E-GOV QUAL - Agustin Setiyorini (Universitas Janabadra, 2018)
The Education Office of Youth and Sports is one of the institutions in KulonProgo Regency Government which is engaged in education, youth, sports and quality improvement of human resources education in KulonProgo Regency. The Office of Youth and Sports Education has developed an information system online through the website. But since the beginning of the website has not been evaluated, so the Office of Youth and Sports Education does not know how the quality of the website from the user. The purpose of this study is to evaluate the website of the Education Office of Youth and Sports KulonProgo District and provide advice to improve the quality of the Education Office of Youth and Sports KulonProgo. Limitation of variables in this study is the method used to complete this evaluation is the E-GovQual Method. This research is empirical contribution research. This research only produces data which is then processed.The user data is obtained by spreading the questionnaire based on 6 dimension on E-GovQual which is the dimension of ease of use, trust, functionality of environmental interaction, reliability, content and appearance of onformation and supporting. Then the results of the questionnaire are analyzed by Importance Performance Analysis (IPA) method.From the analysis of conformity level, the result shows that the level of conformity shows the value of <100% that is 81.90% That is, the website of the Education Office of Youth and Sports KulonProgo regency has not met the expectations of users. Priority for website improvement or website address attributes (EG4), loading time (EG9), all links work well (EG13), user friendly (EG16) views and user queries are answered quickly (EG20). Keyword : evaluation, quality, website, e-government, e-GovQual, IPA